The more the heavier? Family size and childhood obesity in the U.S. (May 2017) - Datar, Ashlesha
Abstract: Childhood obesity remains a top public health concern and understanding its drivers is important for combating this epidemic. Contemporaneous trends in declining family size and increasing childhood obesity in the U.S. suggest that family size may be a potential contributor, but limited evidence exists. Using data from a national sample of children in the U.S. this study examines whether family size, measured by the number of siblings a child has, is associated with child BMI and obesity, and the possible mechanisms at work. The potential endogeneity of family size is addressed by using several complementary approaches including sequentially introducing of a rich set of controls, subgroup analyses, and estimating school fixed-effects and child fixed-effects models. Results suggest that having more siblings is associated with significantly lower BMI and lower likelihood of obesity. Children with siblings have healthier diets and watch less television. Family mealtimes, less eating out, reduced maternal work, and increased adult supervision of children are potential mechanisms through which family size is protective of childhood obesity. Highlights: We examine the link between number of siblings and child BMI and obesity in the U.S. Having more siblings is significantly protective of higher BMI and obesity. Children with more siblings have healthier diets and watch less television. Potential mechanisms include family mealtimes, eating out, and adult supervision.